Isolation of Mycobacterium lepromatosis and Development of Molecular Diagnostic Assays to Distinguish Mycobacterium leprae and M. lepromatosis. (16th November 2019) - Sharma, Rahul; Singh, Pushpendra; McCoy, Rajiv C; Lenz, Shannon M; Donovan, Kelly; Ochoa, Maria T; Estrada-Garcia, Iris; Silva-Miranda, Mayra; Jurado-Santa Cruz, Fermin; Balagon, Marivic F; Stryjewska, Barbara; Scollard, David M; et al.
Abstract: Background: Mycobacterium leprae was thought to be the exclusive causative agent of leprosy until Mycobacterium lepromatosis was identified in a rare form of leprosy known as diffuse lepromatous leprosy (DLL). Methods: We isolated M. lepromatosis from a patient with DLL and propagated it in athymic nude mouse footpads. Genomic analysis of this strain (NHDP-385) identified a unique repetitive element, RLPM, on which a specific real-time quantitative polymerase chain reaction assay was developed. The RLPM assay, and a previously developed RLEP quantitative polymerase chain reaction assay for M. leprae, were validated as clinical diagnostic assays according to Clinical Laboratory Improvement Amendments guidelines. We tested DNA from archived histological sections, patient specimens from the United States, Philippines, and Mexico, and US wild armadillos. Results: The limit of detection for the RLEP and RLPM assays is 30 M. leprae per specimen (0.76 bacilli per reaction; coefficient of variation, 0.65%–2.44%) and 122 M. lepromatosis per specimen (3.05 bacilli per reaction; 0.84%–2.9%), respectively. In histological sections (n = 10), 1 lepromatous leprosy (LL), 1 DLL, and 3 Lucio reactions contained M. lepromatosis ; 2 LL and 2 Lucio reactions contained M. leprae ; and 1 LL reaction contained both species. M. lepromatosis was detected in 3 of 218 US biopsy specimens (1.38%). All Philippines specimens (n = 180) were M. lepromatosis negative and M. leprae positive. Conversely, 15 of 47 Mexican specimens (31.91%) were positive for M. lepromatosis, 19 of 47 (40.43%) were positive for M. leprae, and 2 of 47 (4.26%) contained both organisms. All armadillos were M. lepromatosis negative. Conclusions: The RLPM and RLEP assays will aid healthcare providers in the clinical diagnosis and surveillance of leprosy. Abstract : Mycobacterium lepromatosis was isolated and propagated in mouse footpads. We developed a real-time polymerase chain reaction (PCR) assay using a unique repetitive element, RLPM. We validated this and the RLEP PCR Mycobacterium leprae assay for the clinical diagnosis of leprosy.